Environmental Management Policy of the Municipal Government of Lima and its impact on environmental attitude of the population of Lima 2013-2014 - Valera Chota, Candy (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2019)
This study deals with data based on the opinions of the population of Metropolitan Lima (18-65 years), about the impact of the Environmental Management Policy on the environmental attitude, each citizen perceives reality from different perspectives, expert on the impact of their behavior, it puts in its inner self evaluative aspects, reflecting it in a conscious behavior that it adopts according to its interest, opinions, feelings, preferences; evolving according to their experiences, they demonstrated a sense of belonging and appreciation of their surroundings, so that love towards a place, ancestral knowledge about the environment, involvement and information generate value effects.